SAT0430 SECUKINUMAB EFFECTIVENESS IN 1543 PATIENTS WITH PSORIATIC ARTHRITIS TREATED IN ROUTINE CLINICAL PRACTICE IN 13 EUROPEAN COUNTRIES IN THE EuroSpA RESEARCH COLLABORATION NETWORK. (2nd June 2020) - Michelsen, B.; Georgiadis, S.; DI Giuseppe, D.; Loft, A. G.; Nissen, M.; Iannone, F.; Pombo-Suarez, M.; Mann, H.; Rotar, Z.; Eklund, K.; Kvien, T. K.; Santos, M. J.; et al.
Abstract : Background: There is a lack of real-life evidence on secukinumab effectiveness in psoriatic arthritis (PsA) patients. Objectives: To assess the real-life 6- and 12-month secukinumab retention rates and proportions of patients in remission/low disease activity (LDA) overall, and by prior biologic disease-modifying anti-rheumatic drug (bDMARD)/targeted synthetic (ts)DMARD use. Methods: Data from PsA patients treated with secukinumab in routine care from 13 countries in the European Spondyloarthritis (EuroSpA) Research Collaboration Network were pooled. Patients started secukinumab ≥12 months before date of datacut. Crude and LUNDEX adjusted (crude value adjusted for drug retention) 28-joint Disease Activity index for PSoriatic Arthritis (DAPSA28) and 28-joint Disease Activity Score with CRP (DAS28CRP) remission and LDA rates were calculated. Group comparisons between b/tsDMARD naïve, 1 prior and ≥2 prior b/tsDMARD users were done with ANOVA, Kruskal-Wallis, Chi-square or Kaplan-Meier analyses with log-rank test, as appropriate. Results: A total of 1543 PsA patients were included (Table 1 ). b/tsDMARD naïve patients had shorter time since diagnosis, higher baseline disease activity, a higher proportion were men and a higher proportion achieved remission. Overall 6/12-month secukinumab retention rates were 86%/74% and significantly higher in b/tsDMARD naïve patients at 12, but not 6 months (Table 2, Figure). Overall, crude 6- and 12-month DAPSA28≤4/DAS28CRP<2.6 were achieved by 13%/34% and 11%/39% of the patients, respectively. Conclusion: In this real-life study of 1543 patients with PsA in 13 European countries 12-month secukinumab retention was high, and significantly higher for b/tsDMARD naïve patients. Overall, a higher proportion of bionaïve than previous b/tsDMARD users achieved remission, regardless of remission criteria. Acknowledgments: Novartis and IQVIA for supporting the EuroSpA RCN Disclosure of Interests: Brigitte Michelsen Grant/research support from: Research support from Novartis, Consultant of: Consulting fees Novartis, Stylianos Georgiadis Grant/research support from: Novartis, Daniela Di Giuseppe: None declared, Anne Gitte Loft Grant/research support from: Novartis, Consultant of: AbbVie, MSD, Novartis, Pfizer and UCB, Speakers bureau: AbbVie, MSD, Novartis, Pfizer and UCB, Michael Nissen Grant/research support from: Abbvie, Consultant of: Novartis, Lilly, Abbvie, Celgene and Pfizer, Speakers bureau: Novartis, Lilly, Abbvie, Celgene and Pfizer, Florenzo Iannone Consultant of: Speaker and consulting fees from AbbVie, Eli Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, MSD, Speakers bureau: Speaker and consulting fees from AbbVie, Eli Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, MSD, Manuel Pombo-Suarez Consultant of: Janssen, Lilly, MSD and Sanofi., Speakers bureau: Janssen, Lilly, MSD and Sanofi., Heřman Mann: None declared, Ziga Rotar Consultant of: Speaker and consulting fees from Abbvie, Amgen, Biogen, Eli Lilly, Medis, MSD, Novartis, Pfizer, Roche, Sanofi., Speakers bureau: Speaker and consulting fees from Abbvie, Amgen, Biogen, Eli Lilly, Medis, MSD, Novartis, Pfizer, Roche, Sanofi., Kari Eklund Consultant of: Celgene, Lilly, Speakers bureau: Pfizer, Roche, Tore K. Kvien Grant/research support from: Received grants from Abbvie, Hospira/Pfizer, MSD and Roche (not relevant for this abstract)., Consultant of: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Paid instructor for: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Speakers bureau: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Maria Jose Santos Speakers bureau: Novartis and Pfizer, Björn Gudbjornsson Speakers bureau: Novartis and Amgen, Catalin Codreanu Consultant of: Speaker and consulting fees from AbbVie, Accord Healthcare, Alfasigma, Egis, Eli Lilly, Ewopharma, Genesis, Mylan, Novartis, Pfizer, Roche, Sandoz, UCB, Speakers bureau: Speaker and consulting fees from AbbVie, Accord Healthcare, Alfasigma, Egis, Eli Lilly, Ewopharma, Genesis, Mylan, Novartis, Pfizer, Roche, Sandoz, UCB, Sema Yilmaz: None declared, Johan K Wallman Consultant of: AbbVie, Celgene, Eli Lilly, Novartis and UCB Pharma, Cecilie Heegaard Brahe Grant/research support from: Novartis, Burkhard Moeller: None declared, Ennio Giulio Favalli Consultant of: Consultant and/or speaker for BMS, Eli-Lilly, MSD, UCB, Pfizer, Sanofi-Genzyme, Novartis, and Abbvie, Speakers bureau: Consultant and/or speaker for BMS, Eli-Lilly, MSD, UCB, Pfizer, Sanofi-Genzyme, Novartis, and Abbvie, Carlos Sánchez-Piedra: None declared, Lucie Nekvindova: None declared, Matija Tomsic: None declared, Nina Trokovic: None declared, Eirik kristianslund: None declared, Helena Santos Speakers bureau: AbbVie, Eli-Lilly, Janssen, Pfizer, Novartis, Thorvardur Love: None declared, Ruxandra Ionescu Consultant of: Consulting fees from Abbvie, Eli-Lilly, Novartis, Pfizer, Roche, Sandoz, Speakers bureau: Consulting and speaker fees from Abbvie, Eli-Lilly, Novartis, Pfizer, Roche, Sandoz, Yavuz Pehlivan: None declared, Gareth T. Jones Grant/research support from: Pfizer, AbbVie, UCB, Celgene and GSK., Irene van der Horst-Bruinsma Grant/research support from: AbbVie, Novartis, Eli Lilly, Bristol-Myers Squibb, MSD, Pfizer, UCB Pharma, Consultant of: AbbVie, Novartis, Eli Lilly, Bristol-Myers Squibb, MSD, Pfizer, UCB Pharma, Lykke Midtbøll Ørnbjerg Grant/research support from: Novartis, Mikkel Ǿstergaard Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Merck, and Novartis, Consultant of: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB, Merete L. Hetland Grant/research support from: BMS, MSD, AbbVie, Roche, Novartis, Biogen and Pfizer, Consultant of: Eli Lilly, Speakers bureau: Orion Pharma, Biogen, Pfizer, CellTrion, Merck and Samsung Bioepis